The Impact of Predicted Climate Change on Groundwater Resources in a Mediterranean Archipelago: A Modelling Study of the Maltese Islands - Michele De Biase (MDPI AG, 2021)
The effects of changes in climate predicted for 2100—reduction in recharge, increase in water demand and sea-level rise—on groundwater volume and saltwater intrusion have been quantified in the Maltese Islands, an archipelago located at the center of the Mediterranean Sea. A three-dimensional density dependent and heterogeneous model, working in transient conditions, was developed based on morphological and geological information. The hydraulic conductivity and porosity of the lithological formations were derived from previous tests and studies conducted on the islands. The complex fault system intersecting the area has also been included in the model. The results show that among the three considered factors affecting groundwater resources, the most significant is the increase in water demand, which is closely followed by the decrease in groundwater recharge. Sea-level rise plays a marginal role. The 80-year simulation period showed that these combined impacts would cause a loss of more than 16% of groundwater volume.